Dynamic simulation of electrons in the injector of sealed vacuum chamber of industrial betatrons; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Shestak A. P. Aleksandr Pavlovich; Malikov E. L. Evgeny Lvovich (L'vovich); Sukharnikov K. V. Konstantin Vladimirovich; Rychkov M. M. Maksim Mikhailovich; Kuimova M. V. Marina Valerievna (2015, 2015)
Title screen